Synergistic Effect of Cinnamon Essential Oil (Cinnamomum burmannii) and Doxorubicin on T47D Cells Correlated with Apoptosis Induction - Etyk Yunita Anjarsari; Nita Kristina; Yonika Arum Larasati; Dyaningtyas Dewi Pamungkas Putri; Edy Meiyanto (Indonesian Society for Cancer Chemoprevention, 2013)
Cinnamon (Cinnamomum burmannii) shows anticancer activity in several types of cancer cells. The aim of this study is to observe the cytotoxic activity of cinnamon essential oil (CEO) solely and its combination with doxorubicin, also the ability of the combination to induce apoptosis on T47D breast cancer cells. The CEO was prepared through distillation of dry cinnamon bark. Cytotoxic assay was performed by using MTT assay and apoptosis determination was done by using double staining with ethidium bromide and acridine orange. The result showed that CEO exhibited cytotoxic effect on T47D cells with IC50 values of 75 µg/ml. Moreover, CEO showed synergist effect with doxorubicin. The lowest combination index (CI) with CI values of 0,37 was obtained by combination of doxorubicin-CEO 37,5 µg/ml-1,25 µM. Treatment with CEO solely and its combination with doxorubicin showed apoptosis induction on T47D cells. The results of this study indicate the potency of CEO to be developed as co-chemotherapeutic agent of doxorubicin on breast cancer. Keywords: cinnamon essential oil, doxorubicin, T47D cells, combination cytotoxic